The formation of a dynamic model of synchronous generator with thyristor voltage regulaton - Захарченко, В. А.; Енчев, С. В.; Красношапка, Н. Д.; Ильченко, С. С.; Козуб, В. В. (Problems of Informatization and Control, 2012)
The article deals with the issue of automatic control of threephase alternating voltage power supply system of the aircraft and the formation of a dynamic model of aircontactless synchronous generator with thyristor voltage regulator